Green Credit, Bank Social Responsibility Dan Kinerja Keuangan Perbankan di Indonesia - Mustika, Venna Maulida; Putri, Shara Amelia; Wahyuni, Sri; Sari, Dewi Maya (Jurnal Akuntansi dan Keuangan, 2025)
The study aims to examine the relationship between green credit, bank social responsibility, and the financial performance of banks in Indonesia. Green credit refers to loans provided by banks to sectors that contribute to sustainable development and the environment. Bank social responsibility includes activities conducted by banks to support social and environmental sustainability. This research involves collecting secondary data from banking financial statements and sustainability reports of banks in Indonesia for the year 2022. The data is analyzed using Multiple Regression Analysis. The results show that green credit, proxied by CAR (Capital Adequacy Ratio) and LDR (Loan to Deposit Ratio), is found to affect the financial performance of banks, while ROA (Return on Assets) does not have an effect. Meanwhile, bank social responsibility, proxied by IER (Investment Efficiency Ratio), is found not to affect the financial performance of banks in Indonesia.